2010
DOI: 10.1136/bmj.c5814
|View full text |Cite
|
Sign up to set email alerts
|

Adoption, non-adoption, and abandonment of a personal electronic health record: case study of HealthSpace

Abstract: Objective To evaluate the policy making process, implementation by NHS organisations, and patients' and carers' experiences of efforts to introduce an internet accessible personal electronic health record (HealthSpace) in a public sector healthcare system. Design Mixed method, multilevel case study. Setting English National Health Service; the basic HealthSpace technology (available throughout England) and the advanced version (available in a few localities where this option had been introduced) were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
298
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(302 citation statements)
references
References 33 publications
4
298
0
Order By: Relevance
“…facilitating prescription ordering, 66 appointment booking 67,68 and patients' access to their online record 69 ) have demonstrated proof of concept. [70][71][72] However, such portals are often not widely used by patients beyond the research setting.…”
Section: Online Portalsmentioning
confidence: 99%
See 1 more Smart Citation
“…facilitating prescription ordering, 66 appointment booking 67,68 and patients' access to their online record 69 ) have demonstrated proof of concept. [70][71][72] However, such portals are often not widely used by patients beyond the research setting.…”
Section: Online Portalsmentioning
confidence: 99%
“…In reality, the literature on national roll-outs of 'transformational' IT projects in health care suggests that this assumption may be overoptimistic. 69 Indeed, just because a DOI: 10.3310/hsdr06210 HEALTH SERVICES AND DELIVERY RESEARCH 2018 VOL. 6 NO.…”
Section: Theme 5: Roll-out and Scale-upmentioning
confidence: 99%
“…7 Qualitative evidence indicates that patients are conscious not to be seen to bombard their GP with emails, wishing to maintain a good relationship with their GP, which counteracts perceptions about possible patient behaviour. 8 With regard to safety, the Cochrane review found no evidence of harm caused by email interventions. In addition, security is often stated as a concern, but other industries routinely conduct transactions of a confidential nature via email, for example banking and insurance.…”
Section: What Are the Concerns?mentioning
confidence: 99%
“…Complexity of developing DOI reference number: 10.18293/SEKE2016-064 these software systems is well-known in the literature for many reasons, including heterogeneity of data and issues with interoperability between legacy systems [1], and design and architecture problems [2]. In addition, health applications are sensitive to important non-functional requirements, such as performance, security and safety of data [3] [4]. Therefore, developing and managing health information systems is a hard task.…”
Section: Introductionmentioning
confidence: 99%